Modified Stage Grouping of Diffuse Large B-Cell Lymphoma Involving the Same Side of the Diaphragm in the Rituximab Era - Jeong, Hyehyun; Cho, Hyungwoo; Hong, Jung Yong; Lee, Dae Ho; Kim, Shin; Lee, Kyoungmin; Kang, Eun Hee; Park, Jung Sun; Ryu, Jin Sook; Huh, Jooryung; Suh, Cheolwon (Frontiers in Oncology, 2022)
Among patients with diffuse large B-cell lymphoma (DLBCL) involving the same side of the diaphragm, the prognostic implication of extranodal disease or its contiguity with the nodal lesion remains unclear. In this study, patients with DLBCL treated with R-CHOP whose disease is limited to the same side of the diaphragm were included. Survival was assessed by the presence, contiguity, and the number of extranodal lesions. Among the 508 patients included, overall survival (OS) and progression-free survival (PFS) did not differ according to the presence of single extranodal involvement or its anatomical contiguity with the nodal lesion. However, patients with ≥2 extranodal involvement showed significantly inferior OS and PFS. We re-classified these patients into two groups; modified stage IIEe (≥2 extranodal involvement, n=92) and modified stage II (nodal or single extranodal involvement irrespective of anatomical contiguity, n=416). This modified staging showed improved prognostic performance based on the time-dependent ROC curve compared with Ann Arbor staging. In conclusion, in patients with DLBCL on the same side of the diaphragm, survival outcomes were associated with the number of extranodal involvement, but not with the contiguity of the lesions or presence of a single extranodal involvement. The modified staging (modified stages IIEe and II) can be considered.